The conservation and ecology of the British Virgin Islands endemic tree, Vachellia anegadensis. Issue 1 (20th January 2022) - Bárrios, Sara; Dufke, Maria; Hamilton, Martin; Cowan, Robyn; Woodfield-Pascoe, Nancy; Dalsgaard, Bo; Hawkins, Julie; Clubbe, Colin
Abstract: Numerous island species have gone extinct and many extant, but threatened, island endemics require ongoing monitoring of their conservation status. The small tree Vachellia anegadensis was formerly thought to occur only on the limestone island of Anegada in the British Virgin Islands and was categorized as Critically Endangered. However, in 2008 it was discovered on the volcanic island of Fallen Jerusalem, c. 35 km from Anegada, and in 2018 it was recategorized as Endangered. To inform conservation interventions, we examined the species' distribution, genetic population structure, dependency on pollinators and preferred habitat, and documented any threats. We found V. anegadensis to be locally widespread on Anegada but uncommon on Fallen Jerusalem and established that geographical location does not predict genetic differentiation amongst populations. Vachellia anegadensis produces the highest number of seed pods when visited by animal pollinators, in particular Lepidoptera. Introduced animals and disturbance by humans appear to be the main threats to V. anegadensis, and in situ conservation is critical for the species' long-term survival.